La resiliencia asociado al estrés debido al consumo de alcohol de los padres, de los/las adolescentes del Bachillerato de la Unidad Educativa Fiscomisional La Dolorosa del cantón Chaguarpamba provincia de Loja. - Carrión Reyes, Mónica Elizabeth (2017)
The following investigation research showed that, the resilience associated to stress, due to the consumption of alcohol by parents, from baccalaureate students at “La Dolorosa” High School from Chaguarpamba canton, Province of Loja during the period of 2015-2016. The main objective was to determine the resilience associated to stress due to the consumption of alcohol by parents, the investigation responded to a social scientific cross-sectional study focusing on Quantity-Qualitative, in which 130 students participated. A survey was applied in order to identify the variables on alcohol consumption, resilience test and vulnerability test to stress. The results obtained stand out, that, a 58% of teenagers are children of parent who consume alcohol, a 59% showed to be slightly resilient and a 41% are not resilient meanwhile 61% of students presented a vulnerability to stress and a 37% are seriously vulnerable to stress. Therefore awareness strategies are applied through a psychoeducational proposal that can allows an access to timely information and precise to avoid stress in adolescents/teenagers by alcohol consumption in parents improving the resilience capacity that the individual has in order to strengthen personal and family coping strategies. Key-words:- resilience, stress, adolescents/teenagers, alcohol consumption.